MEDICINAL PROPERTIES OF LYCHEE PLANT (American Journal of Interdisciplinary Research and Development, 2022)
This article provides valuable scientific information about the Chinese lychee plant (litchi chinensis) in folk medicine, its origin and distribution area, medicinal properties, and cultivation technology.